1993
DOI: 10.1002/1097-0142(19930915)72:6<1894::aid-cncr2820720617>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Germ cell tumors of the mediastinum. A 30-year experience

Abstract: Background. The records of 98 consecutive patients (58 males and 40 females; median age, 27 years; age range, 2-64 years) who presented with a primary germ cell tumor (GCT) of the mediastinum between January 1960 and December 1990 were reviewed. There were 45 mature teratomas, 8 immature teratomas, 16 pure seminomas, and 24 malignant nonseminomatous GCT (MNSGCT).Results. All patients with mature teratomas were cured by radical resection alone, except one patient who died intraoperatively. Among the eight patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(116 citation statements)
references
References 25 publications
(1 reference statement)
4
109
0
3
Order By: Relevance
“…As for benign teratomas, a female predominance (a 1.64:1 ratio). This was comparable with the female predominance (a 1.27:1 ratio) reported by Lewis et al 7 and Dulmet et al 9 (a 2.05:1 ratio). Clinical symptoms and physical examination contributed little to making a diagnosis.…”
Section: Benign Mature Teratomassupporting
confidence: 90%
See 3 more Smart Citations
“…As for benign teratomas, a female predominance (a 1.64:1 ratio). This was comparable with the female predominance (a 1.27:1 ratio) reported by Lewis et al 7 and Dulmet et al 9 (a 2.05:1 ratio). Clinical symptoms and physical examination contributed little to making a diagnosis.…”
Section: Benign Mature Teratomassupporting
confidence: 90%
“…A VATS excision should be used for relatively small tumors that do not severely adhere to the adjacent tissues. Dulmet et al 9 reported that immature teratomas comprised 8 of 98 GCT cases. These patients were given additional chemotherapy and/or irradiation.…”
Section: Benign Mature Teratomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Such patients appear to represent a clinically and biologically distinct disease entity (Nichols et al, 1985(Nichols et al, , 1987(Nichols et al, , 1990aHartmann et al, 2000b, (Saxman et al, 1994, Loehrer et al, 1998Hartmann et al, 2001a). Historically, the incorporation of cisplatin into chemotherapy regimens has yielded survival rates of approximately 30 -40% in retrospective analyses (Garnick et al, 1983;Logothetis et al, 1985;Delgado et al, 1993;Dulmet et al, 1993;Toner et al, 1991; International germ cell consensus classification, 1997). Two prospective series based on 31 and 41 patients reported a long-term survival rate of 450% following conventional cisplatin-based chemotherapy plus secondary surgery (Nichols et al, 1990b, Bukowski et al, 1993.…”
Section: Discussionmentioning
confidence: 99%